THE CRITICAL FREQUENCY OF THE IONOSPHERIC F2-LAYER AS OBTAINED FROM IONOSONDE DATA AND OBSERVATIONS OF SOLAR RADIO BURSTS - L. O. Stanislavsky; I. M. Bubnov; S. M. Yerin; A. V. Zalizovski; V. M. Lisachenko (Radio Physics and Radio Astronomy, 2022)
Subject and Purpose. Studying the time variations shown by the critical frequencies of the ionospheric F2 layer through comparative analysis of ionosonde data and observations of type III solar radio bursts.